2017
DOI: 10.1123/jsep.2017-0056
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulation and Implicit Attitudes Toward Physical Activity Influence Exercise Behavior

Abstract: Dual-process models of health behavior posit that implicit and explicit attitudes independently drive healthy behaviors. Prior evidence indicates that implicit attitudes may be related to weekly physical activity (PA) levels, but the extent to which self-regulation attenuates this link remains unknown. This study examined the associations between implicit attitudes and self-reported PA during leisure time among 150 highly active young adults and evaluated the extent to which effortful control (one aspect of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…To illustrate, two studies indicate that the relationship between implicit attitudes and physical activity could be moderated by dispositional variables. Padin et al (2017) found that implicit attitudes toward exercise were associated to physical activity among students with low, but not high, effortful control (one aspect of self-regulation). It may be that individuals with higher capacity for self-regulation relied less on implicit attitudes toward physical activity to guide behavior than those with lower self-regulation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To illustrate, two studies indicate that the relationship between implicit attitudes and physical activity could be moderated by dispositional variables. Padin et al (2017) found that implicit attitudes toward exercise were associated to physical activity among students with low, but not high, effortful control (one aspect of self-regulation). It may be that individuals with higher capacity for self-regulation relied less on implicit attitudes toward physical activity to guide behavior than those with lower self-regulation.…”
Section: Discussionmentioning
confidence: 96%
“…To this point, studies have demonstrated that implicit attitudes are directly associated with the amount of physical activity people engage in, both selfreported or measured with accelerometers, even after controlling for the variability explained by explicit processes (see Rebar et al, 2016;Schinkoeth & Antoniewicz, 2017, for reviews). Indeed, several studies found that implicit and explicit attitudes toward physical activity are mostly unrelated (e.g., Brand & Antoniewicz, 2016;Hyde, Doerksen, Ribeiro, & Conroy, 2010) and independently associated with physical activity behavior (e.g., Calitri et al, 2009;Chevance, Caudroit et al, 2017;Padin et al, 2017). However, to the best of our knowledge, there is no evidence yet of indirect associations between implicit attitudes and physical activity through interactions with explicit processes (see for example Muschalik, Elfeddali, Candel, & de Vries, 2018;Chevance, Caudroit et al, 2018), or other implicit processes (e.g., attentional bias, approach-avoidance tendencies, see…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, depressed individuals appear to have deficits in self-regulation [55][56][57]. A combination of negative attitudes and poor self-regulatory skills, in particular, may leave a depressed individual especially vulnerable to decreased physical activity, as previous findings suggest that individuals with poor self-regulatory capacity and negative implicit attitudes have shorter average workout durations [58].…”
Section: Discussionmentioning
confidence: 97%
“…Researchers have found that executive functioning moderated relationships between automatic approach and avoid tendencies to exercise and activity behaviour or intentions to be active (Chevance, Yannick, Heraud, & Boiche, 2018; Cheval, Sarrazin, Isoard-Gautheur, Radel, & Friese, 2016) (48,49). Others have also found that participants with lower automatic evaluations, combined with less ability to control their actions exercised for less time, but this relationship did not exist for participants with greater ability to exert cognitive control (Padin, Emery, Vasey & Kiecolt-Glaser, 2017) (26). The results of the current study may indicate that participants who were less motivated by guilt or obligation and positive automatic evaluations were more motivated to be active for health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Hyde and colleagues found that introspective access moderated relationships between (IEDs) and (PA) (6) while Berry and colleagues showed a moderating role for identi ed regulations related to (IEDs) measuring associations with appearance (7). Eeffortful control (one aspect of self-regulation) was found to moderate associations between implicit evaluations and self-reported (PA) during leisure time among 150 highly active young adults (26).…”
Section: Introductionmentioning
confidence: 99%